2016
DOI: 10.1371/journal.pone.0151094
|View full text |Cite
|
Sign up to set email alerts
|

Functional Visual Acuity of Early Presbyopia

Abstract: PurposeTo evaluate visual function in patients with early presbyopia using the functional visual acuity (FVA) test.MethodsThis study included 27 eyes of 27 healthy older volunteers (mean age, 44.1 ± 2.6 years) and 14 eyes of 14 healthy young volunteers (mean age, 28.4±4.8 years). The distance-corrected visual acuity (DCVA), distance-corrected near VA (DCNVA), subjective amplitude of accommodation (AA), and distance and near pupillary diameters were measured. The distance FVA and distance-corrected near FVA (DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Subsequent studies showed that the FVA measurement is also applicable for the analysis of visual function accompanying refractive surgery, 20,[56][57][58] contact lens wearing, 59,60 cataract and cataract-related disease, 61,62 retinal disease, 63,64 glaucoma, 65 amblyopia, 66 presbyopia, 67 and vehicle driving. 68,69 FVA reflects not only visual function related to tear dynamics, but also visual function related to quick recognition of the target, according to the measurement condition requiring a judgment time within the limited set time.…”
Section: Future Directionsmentioning
confidence: 99%
“…Subsequent studies showed that the FVA measurement is also applicable for the analysis of visual function accompanying refractive surgery, 20,[56][57][58] contact lens wearing, 59,60 cataract and cataract-related disease, 61,62 retinal disease, 63,64 glaucoma, 65 amblyopia, 66 presbyopia, 67 and vehicle driving. 68,69 FVA reflects not only visual function related to tear dynamics, but also visual function related to quick recognition of the target, according to the measurement condition requiring a judgment time within the limited set time.…”
Section: Future Directionsmentioning
confidence: 99%
“…The FVA measurement has been reported to detect early presbyopia more sensitively than the usual VA measurement 17 . The AS-28 (Kowa Co. Ltd., Aichi, Japan) was used to measure the FVA.…”
Section: Methodsmentioning
confidence: 99%
“…It is speculated that both KVA and FVA are important for major integrated visual function working with continuous fixation. FVA may deteriorate in cataract, posterior capsule opacification, DE and age-related macular degeneration 23–28. These are treatable eye diseases and adequate ophthalmological treatments are recommended for drivers suffering these diseases to achieve the best possible visual performance.…”
Section: Discussionmentioning
confidence: 99%